Travaux collectifs à distance et mobilisation des apprenants : l'exemple d'un diplôme d'université en ligne - Patrick Lemaire; Viviane Glikman (Centre National d'Enseignement à Distance, 2016)
This paper first describes the characteristics of the online learning system that was studied and analyses how learners participate in the various activities on which it is based (information sharing, discussions on forums, collaborative tasks, virtual meetings). It thus aims to establish how these activities and the support provided contribute in fostering persistence and involvement in the learning process, and the creation of a learning community. The data gathered and the points of view the learners expressed enable conclusions to be drawn regarding the engagement, the friendliness and trust that were developed. The paper concludes on the interest of the chosen approach and on its relatively few weaknesses, along with pointers to improving its effectiveness and a consideration of its potential for working in other contexts.